Crystal-to-crystal thermal phase transition amongst dimorphs of hexa-O-p-toluoyl-myo-inositol conserving two-dimensional isostructurality - Gonnade, Rajesh G.; Bhadbhade, Mohan M.; Shashidhar, Mysore S. (Crystengcomm, 2010)
Triclinic (P-1) crystals of hexa-O-p-toluoyl-myo-inositol obtained from common organic solvents exhibited single crystal-to-single crystal irreversible phase transition centered at similar to 250 degrees C. The transformation of these crystals to monoclinic P2(1)/n form was revealed using DSC and X-ray diffraction studies. The latter crystals could also be produced by melt crystallization. Crystal structure analysis revealed that the molecules in both forms are linked via bifurcated C-H center dot center dot center dot O interactions to make almost identical centrosymmetric dimers. The neighbouring dimers are bridged via C-H center dot center dot center dot O and aromatic pi center dot center dot center dot pi stacking interactions to create two-dimensional isostructural assemblies. The difference in the two crystal forms arises from linking of the centrosymmetric dimers along the third dimension; the dimers are centrosymmetrically bridged in the triclinic form, while they have n-glide relationship in the monoclinic form. Comparison of the dimorph structures further revealed that they are actually an excellent case of morphotropism since dimorphs are related by non crystallographic rotation and translation of their basic motif (centrosymmetric dimers) that transforms the triclinic (P-1) phase to a monoclinic (P2(1)/n) phase.